Fluvial Geomorphology - Jongkar, Grinang; Edward, Muol; Gabriel Tonga, Noweg; Anita, Muli; Mustafa Kamal, Mohd Faizal; Cindy, Peter; Chai, Hui Ping; Lai, wei seng; Nur Ezaimah, Idris; Hafida, Bolhen; Lee, Nyanti; Ling, Teck Yee; et al. (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
Physical characteristics of a stream is a crucial variable shaping biological communities and ecosystem functions. Therefore, fluvial geomorphological forms (landform, shape, size and networks) and processes (stream flow, sediment erosion, transport and deposition) have been central to ecological research in describing interrelationships between river systems and their biodiversity. The topic, however, has not been emphasized in Borneo.